2023
DOI: 10.3390/ijms24032962
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Roles of the Hedgehog Signaling Pathway during T-Cell Lymphopoiesis and in T-Cell Acute Lymphoblastic Leukemia (T-ALL)

Abstract: The Hedgehog (HH) signaling network is one of the main regulators of invertebrate and vertebrate embryonic development. Along with other networks, such as NOTCH and WNT, HH signaling specifies both the early patterning and the polarity events as well as the subsequent organ formation via the temporal and spatial regulation of cell proliferation and differentiation. However, aberrant activation of HH signaling has been identified in a broad range of malignant disorders, where it positively influences proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 258 publications
2
4
0
Order By: Relevance
“…Given the importance of Hh signaling in mediating T cell development and cytotoxic functions 34,37,36 , we confirmed differential RNA expression in CD8 T cells in disparate liver fibrosis contexts in HCV infection by qPCR analysis of PTCH1 and GLI1 mRNA. In isolated CD8 T cells stimulated with anti-CD3/CD28 antibodies for 16h, PTCH1 and GLI1 mRNA expression was elevated in HCV + individuals relative to uninfected healthy controls, and PTCH1 mRNA expression levels associated with fibrosis severity (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Given the importance of Hh signaling in mediating T cell development and cytotoxic functions 34,37,36 , we confirmed differential RNA expression in CD8 T cells in disparate liver fibrosis contexts in HCV infection by qPCR analysis of PTCH1 and GLI1 mRNA. In isolated CD8 T cells stimulated with anti-CD3/CD28 antibodies for 16h, PTCH1 and GLI1 mRNA expression was elevated in HCV + individuals relative to uninfected healthy controls, and PTCH1 mRNA expression levels associated with fibrosis severity (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Hh signaling engagement participates in facilitating growth and treatment resistance across a wide variety of cancers [102][103][104][105][106][107]. This is also the case in rhabdomyosarcoma [88,[108][109][110][111][112][113].…”
Section: Itraconazole and Hhmentioning
confidence: 97%
“…As reviewed by Martelli et al [116], therapeutically relevant signaling pathways interacting with Hh signaling have been identified in T-ALL cells such as the Notch pathway. This plays an important role in leukemic cell growth, survival, and rewired metabolism in both T-ALL [117,118] and B-ALL cells [119].…”
Section: Hedgehog Signalingmentioning
confidence: 99%
“…Inhibition of Akt or ERK pathways decreased GLI1 expression levels, suggesting that suggesting a positive regulation of GLI1 transcriptional activity and expression by these two pathways [125], the mechanism of which remains to be explored [116]. However, regarding ERK pathway, it has been shown that ERK2 phosphorylates GLI1 at three sites (Ser102, 116,130), leading to weakening of GLI1 binding to SUFU, thereby increasing GLI1 transcriptional activity [126]. Thus, the activation of the Hh signaling pathway by GC may be involved in the activation of multiple cell survival signaling pathways.…”
Section: Hedgehog Signalingmentioning
confidence: 99%